UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA DENGAN MEDIA MODUL PADA MATA PELAJARAN KERJA LAS DI SMK NEGERI 2 KEBUMEN - Akhmad Muzani; Arif Marwanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
This study aims to determine the effect of using the module on students' learning motivation in the subject of welding work. At the same time, to determine the effect of using the module on student achievement in welding work subjects at SMK Negeri 2 Kebumen. The method used in this study is a research method experiment, the implementation of which uses a quasi-experimental type with a nonequivalent control group design. The research was conducted at SMK Negeri 2 Kebumen with a sample of 2 classes, namely class XI TP 1 as a group experiment, class XI TP 2 as the control group. To determine the motivation to learn data collection using observation sheets and questionnaires. While to determine learning achievement data collection in the form of test results carried out before and after the learning process (pretest and posttest). The process of teaching and learning activities in the experimental class uses a module entitled Welding Classroom with the SMAW Process, while the control class uses a lecture learning strategy (conventional). The results showed that the effect of using the module on students' learning motivation is categorized as very high/very positive. Proven from the results of the overall student motivation questionnaire mean is 90.41 and the results of observations with the answer "YES as much as 25. The effect of using the module on student achievement is to improve learning outcomes. It is evident from the experimental class learning outcomes at the pretest, the mean is 52, the median is 52.5, the mode is 46, the highest score is 69, and the lowest score is 34. After using the module, the mean 83, median 83, mode 83, the highest score 97, and the lowest score 60. Calculation of the independent sample test t test with an error rate of 5% shows that t table < tcount (1.669 < 3.619). It was decided that there was a significant difference There is a significant difference between the learning outcomes of the experimental class using module media and the conventional learning control class.